ЖИЙЕН-ЖЫРАЎ АМАНЛЫҚ УЛЫНЫҢ ӨМИРИ ҲӘМ ДӨРЕТИЎШИЛИГИН ЖАҢАША КӨЗҚАРАСТА ҮЙРЕНИЎДИҢ АЙЫРЫМ МӘСЕЛЕЛЕРИ - Алламбергенов, К. (SCIENCE and SOCIETY, 2022)
The article re-analyzes the life and work of the great classic of Karakalpak literature of the XVIII century Jiyen Jirov Amanlik oglu from the point of view of the ideas of national independence on the basis of new data. It is also concluded that Jiyen Jirov was born in 1710 and died in 1784 at the age of 74.